Proselytism without Coercion and without Discrimination against non-Muslims in the Study of Quranic Proselytism Exegesis - Sayed Akhyar; Sufian Suri; Irwanto Irwanto; Andri Nirwana AN (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The reality is that people who are the target of da'wah always reject new da'wah teachings because they compare them with old da'wah teachings that have become a tradition in their lives. The method used in this study is the Systematic Literature Review (SLR) method. The SLR method is used to identify, review, evaluate, and interpret all available research with topic areas of interest to phenomena, with relevant research questions. With the use of the SLR method, a systematic review and identification of journals can be carried out, which in each process follows the steps or protocols that have been set. The results of this research show that in introducing the new Islamic teachings to non-Muslims, all the Prophets used da'wah methods. This da'wah is a way of inviting people to follow the right path for salvation in this world and the hereafter. The approach or method of da'wah taken by the prophets in dealing with their respective people is guided by the da'wah methods outlined by Allah s.w.t as conveyed by the Qur'an. The most prominent characteristics that support the strength of the da'wah movement of the prophets are patience, high will, istiqamah and determination. This characteristic makes them worthy of being given the status of Nabiyullah by Allah subhanahu wata'ala